Association between lncRNA H19 rs217727 polymorphism and the risk of cancer: an updated meta-analysis - Xue Wang; Jialing Zhong; Fang Chen; Kang Hu; Suhong Sun; Yuanxiu Leng; Xumei Chen; Fengjiao Gan; Yana Pan; Qing Luo (BMC, 2019)
Abstract Background We have performed this study to evaluate the association between H19 rs217727 polymorphism and the risk of cancer. Methods An odds ratio (OR) with a 95% confidence interval (CI) was applied to determine a potential association. Results A total of 17 case-control publications were selected. This meta-analysis showed that H19 rs217727 has a significant increased association with cancer risk in allelic, homozygous, heterozygote, dominant and recessive models (T vs C: OR = 1.16, 95% CI = 1.06-1.27, I 2  = 75.7; TT vs CC: OR = 1.29, 95% CI = 1.06-1.56, I 2  = 71.6; CT vs CC: OR = 1.15, 95% CI = 1.01-1.31, I 2  = 75.4; CT + TT vs CC: OR = 1.20, 95% CI = 1.05-1.36, I 2  = 76.5; TT vs CT + CC: OR = 1.22, 95% CI = 1.02-1.45, I 2  = 70.6;). In the subgroup analysis of smoking status, both smokers and nonsmokers showed an increase in cancer risk in allelic, homozygous, dominant and heterozygote models. Conclusion This meta-analysis revealed H19 rs217727 may influence cancer susceptibility.